2016
DOI: 10.4103/1793-5482.165780
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Glasgow Coma Scale and brain computed tomography-scan findings in head trauma patients

Abstract: Background:The study aimed to assess the relationship between computed tomography (CT) scan findings and Glasgow Coma Scale (GCS) score with the purpose of introducing GCS scoring system as an acceptable alternative for CT scan to clinically management of brain injuries in head trauma patients.Materials and Methods:This study was conducted on hospitalized patients with the complaints of head trauma. The severity of the head injury was assessed on admission by the GCS score and categorized as mild, moderate, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
(32 reference statements)
2
23
0
Order By: Relevance
“…A strong association was found between CT positivity and severity of head injury based on GCS score with P < 0.05. CT positivity is higher in severe head injury (GCS ≤ 8) with odds ratio [OR] = 54.702 (95% CI: 25.88-116.943) and in moderate head injury (GCS 9-12) with OR = 7.668 (95% CI: 3.336-17.624), compared to MHI (GCS [13][14][15] as the reference group. This is consistent with findings of Schynoll et al, [20] who reported a strong association of abnormal CT findings with patients with GCS <15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong association was found between CT positivity and severity of head injury based on GCS score with P < 0.05. CT positivity is higher in severe head injury (GCS ≤ 8) with odds ratio [OR] = 54.702 (95% CI: 25.88-116.943) and in moderate head injury (GCS 9-12) with OR = 7.668 (95% CI: 3.336-17.624), compared to MHI (GCS [13][14][15] as the reference group. This is consistent with findings of Schynoll et al, [20] who reported a strong association of abnormal CT findings with patients with GCS <15.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Glasgow Coma Scale (GCS) classified head injuries as minor, moderate, and severe. [15] Around 70%-90% of all head injuries fall in the category of minor head injuries. Computed tomography (CT) has prime importance in the investigation of head injury.…”
Section: Introductionmentioning
confidence: 99%
“…If a good correlation between the CT scan appearance and GCS scoring can be found, then the use of follow-up CT scans would only be recommended in patients with clinical deterioration unexplained by intracranial pressure changes alone. Thus, substantially, lowering the radiation dose and also reducing the cost by preventing unwanted CT scans 12 . At present, there is no updated study regarding the correlation of the Glasgow Coma Scale (GCS) and intracranial injuries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Based on Glasgow Coma Scale (GCS), head injury can be classified as minor, moderate, and severe head injury. [ 2 ] Minor head injury (MHI) constitutes around 70%–90% of all head injuries. [ 3 ] Computed tomography (CT) is the choice of investigation in head injury.…”
Section: Introductionmentioning
confidence: 99%